Chronic myeloid leukemia management during pregnancy: a case report - Lima, Luina Benevides; Moreira-Nunes, Caroline de Fátima Aquino; Mesquita, Felipe Pantoja; de Oliveira, Lais Lacerda Brasil; Bezerra, Emanuel Cintra Austregésilo; da Silva, Emerson Lucena; Duarte, Fernando Barroso; Quixadá, Acy Telles de Souza; de Moraes, Maria Elisabete Amaral; Montenegro, Raquel Carvalho (Brazilian Journal of Case Reports, 2022)
Chronic Myeloid Leukemia (CML) is characterized by the increased and unregulated growth of myeloid cells in bone marrow and accumulation of these cells in blood. Its occurrence during pregnancy is a very rare condition and the correct management is not well stablished yet. We present a case of a 21-year-old female diagnosed with CML during pregnancy. The protocol chose by the doctor was hydroxyurea on second trimester, and interferon-alpha on third trimester. The baby was born healthy and at the expected time. After giving birth, the patient started Imatinib Mesilate (IM) 400mg/day treatment and was able to control the disease.